Intervenção educativa no uso de MNF para alívio da dor no trabalho de parto: ensaio clínico randomizado - Balsells, Marianne Maia Dutra (2023)
The decision on the type of birth comprises a phenomenon that accompanies the entire pregnancy process and generates countless expectations, since pregnancy, and continues to be mentioned even after birth, persisting in the form of memories and feelings, or even in consequences for health. , which become part of your story. Thus, the present study aimed to evaluate the effects of an educational intervention in prenatal care, on women's knowledge, attitude and practice regarding non-pharmacological methods for pain relief during labor and delivery. A Randomized, controlled, blind Clinical Trial was carried out, in which two groups were compared: control group, pregnant women eligible to participate in the study, who received routine guidance from UAPS and maternity professionals; and intervention group, pregnant women who received individual educational intervention using the booklet, during prenatal care, associated with routine guidance from UAPS and maternity professionals, thus totaling 93 women who participated in the study. Randomization was carried out through the simple random allocation of the 11 UAPS that were part of the conglomerate. The population was made up of pregnant women followed in prenatal consultations at UAPS, in the first and second phases. The third phase included the same participants, now postpartum women, admitted to the MEAC, who had a vaginal birth and who received prenatal care at the UAPS. In the intervention group, the educational booklet “What do you know about non pharmacological methods for pain relief during labor and delivery” was used? Let’s find out!”, already validated in the master’s degree. Data collection took place in the city of Fortaleza-CE, in the period between February 2022 and April 2023, in 11 Primary Health Care Units (UAPS) belonging to the Regional Executive Secretariat (SER) III and IV, in a maternity hospital, In Ceara. A face-to-face interview was carried out, using three instruments: sociodemographic and obstetric data, and data on preparation for childbirth; Knowledge, Attitude and Practice Survey; and birth data. The data were compiled and analyzed using the Statistical Package for the Social Sciences (SPSS), version 23.0. It was submitted to the UFC Research Ethics Committee, approved under Opinion No. 4,972,939. In the intragroup analysis, the McNemar Test demonstrated an increase in the proportion of adequate knowledge of women in the GI about MNF for pain relief in the PT and P, when comparing the data between the 1st and 2nd phase (X²(1)=4.762 ; p = 0.027). Cochran's Q Test showed that there are differences in the distributions of "adequate" and "inadequate" knowledge in the IG in the three phases (X²(2) = 10.5; p = 0.005). The pairwise comparison carried out using the Cochran's Q Test showed that the proportion of adequate knowledge in the IG was higher in the 3rd phase than in the 1st and 2nd phases (p=0.004). This study demonstrated that the booklet influenced the increase in knowledge and attitude in the intervention group, however there is not enough evidence to state that the material increased the practice of non-pharmacological methods during labor.